Positive Touch Deprivation during the COVID-19 Pandemic: Effects on Anxiety, Stress, and Depression among Italian General Population - Francesco Bruno; Carlotta Tagliaferro; Sonia Canterini; Valentina Laganà; Marianna Contrada; Chiara Fioravanti; Natalia Altomari; Rebecca Pistininzi; Francesca Tarantino; Alessia Placanica; Ersilia Martina Greco; Francesca Capicotto; et al. (Brain Sciences, 2023)
Physical distancing due to the COVID-19 Pandemic has limited the opportunities for family members, friends, and significant others to show physical affection (i.e., hugs, kisses, caresses, holding hands) during social interactions. The present study investigated the effects of positive touch and psychological distress in 991 Italian participants (Mage = 34.43, SD = 14.27). Results showed the frequency of hugs with the cohabiting partner significantly decreased the symptoms of depression (β = −1.187, p = 0.018, eβ = 0.30, 95% CI = 0.11–0.82), whereas the frequency of caresses with cohabiting relatives predicted the symptoms of anxiety (β = 0.575, p = 0.034, eβ = 1.78, 95% CI = 1.04–3.03). The frequency of hugs (β = −0.609, p = 0.049, eβ = 0.54, 95% CI = 0.30–1.00), and kisses (β = 0.663, p = 0.045, eβ = 1.94, 95% CI = 1.01–3.71) with non-cohabiting relatives predicted the symptoms of anxiety (χ2 = 1.35, df = 5, p = 0.93). These results suggest the importance of positive touch on psychological well-being in the social context.